Device and method for separating all components of wood fiber and improving enzymolysis efficiency
By using an electrothermal reaction unit and a dilute acid-base coupling treatment device in the pretreatment process of lignocellulose, the problems of high costs, environmental pollution and strict equipment requirements in the prior art are solved, and efficient separation of the whole component of lignocellulose and the improvement of enzymatic saccharification efficiency of enzymatic saccharification are achieved.
Patent Information
- Application Number
- CN202411865937.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-18
Smart Images

Figure CN119736158A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomass resource utilization, and particularly relates to a device and method for separating all components of wood fiber and improving enzymolysis efficiency. Background Art
[0002] High demand for clean technologies, sustainable strategies, and eco-friendly processing has led to a resurgence in the development of alternative chemicals and materials that can improve environmental pollution and resource shortages worldwide. Lignocellulosic biomass is a promising renewable resource in the form of agricultural and forestry wastes with great potential for the sustainable production of various high-value biomaterials. The main components of lignocellulosic biomass are hemicellulose, cellulose, and lignin, all of which are recyclable carbon sources. It is estimated that tens of billions of tons of lignocellulose are produced annually worldwide. However, this potential value remains largely untapped due to its complex composition and stubborn cross-linked chemical structure. Therefore, unlocking this potential requires a suitable and efficient separation process that can adapt to the structural complexity of lignocellulose and obtain value from all its major components.
[0003] In the field of biomass resource utilization and biorefining, pretreatment is a key step in the entire process, which can decompose the natural stubborn structure of lignocellulosic biomass and fractionate its three main components. However, due to the contradictory properties of hemicellulose and lignin, that is, hemicellulose is easy to degrade, while lignin is difficult to extract, it is difficult to achieve complete conversion of all components with one-step pretreatment technology. In single pretreatment methods, most studies focus on the strong removal of lignin in pursuit of digestible cellulose-rich substrates. These processes usually lead to the degradation of cellulose / hemicellulose into oligomers, sugar monomers and other small molecule byproducts or inhibitors, which adds additional technical difficulties to their subsequent utilization.
[0004] In order to solve the challenges of easy degradation of cellulose and difficult separation of lignin, processes combining hydrothermal pretreatment with chemical extraction have been proposed to achieve value-added utilization of all components of lignocellulose. The solvent systems used in existing chemical extractions include ionic liquids, low eutectic solvents, organic solvents, and various acid-base systems. These solvents are not only expensive and toxic, but also prone to adverse effects on the environment. Hydrothermal pretreatment is an environmentally friendly, low-cost extraction and separation technology that can depolymerize hemicellulose and soften and swell lignin, providing a more fragile biomass structure for chemical extraction. However, existing hydrothermal pretreatment technologies all rely on reactors or reactors under pressurized and high-temperature environments, which have strict requirements on equipment and are not easy to carry out large-scale production. For example, CN 115142288 A discloses a method for quickly separating all components of lignocellulosic biomass using an alkaline low eutectic solvent, wherein a microwave reactor is used to pretreat a mixed system of lignocellulosic and alkaline low eutectic solvent at a heat treatment temperature of 80-160°C; CN 111154817A discloses a method for efficiently separating and enzymatically hydrolyzing lignocellulose using an ionic liquid-high boiling alcohol composite system, wherein a composite system composed of a proton-type ionic liquid and a high boiling alcohol is used for pretreatment at 100-140°C; CN 111826986 A discloses a method for efficiently separating all components of lignocellulose, wherein a CO2-assisted hydrothermal method is used to achieve the degradation of hemicellulose in lignocellulosic at 180-200°C; and then a low eutectic solvent is used to achieve the separation of cellulose and lignin at 100-140°C. The above-mentioned pretreatment processes are all cutting-edge technologies, but they have the following problems: (1) Existing chemical extraction processes cannot avoid expensive and environmentally unfriendly solvent systems; (2) Traditional hydrothermal treatment equipment requires the use of reactors or reactors to achieve a pressurized high-temperature environment; it is difficult to carry out large-scale processing; (3) The pretreatment temperature of most processes is too high, which easily leads to the formation of inhibitors and affects subsequent separation, saccharification and fermentation. Therefore, there is an urgent need for a device and process for pretreatment of wood fiber raw materials that is both green and environmentally friendly, simple to operate, and can be mass-produced. Summary of the invention
[0005] In order to solve the above problems, the main purpose of the present invention is to provide a device and method for achieving full component separation of wood fiber and improving the efficiency of enzymatic saccharification, thereby overcoming the shortcomings of the prior art.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0007] On one hand, the present invention provides a device for separating all components of wood fiber and improving the efficiency of enzymatic saccharification, the device comprising an electric heat reaction unit 100, a pumping device 200, a stirring device 300, a power supply device 400, and a cooling device 500;
[0008] The electrothermal reaction unit 100 is composed of reaction tubes 101-102, a magnetic core 103, a water cooling plate 104 and an excitation coil 105;
[0009] The magnetic core 103 is a ring-shaped plate-shaped magnetic conductive material with a hole in the middle; the water-cooling plate 104 is a ring-shaped plate-shaped metal material with a hole in the middle, which is placed alternately with the magnetic core; the outer edge of the water-cooling plate 104 is embedded with cooling pipes 201-202 for cooling liquid circulation;
[0010] The water-cooled plate 104 is connected to the cooling device 500 through cooling pipes 201-202; the cooling device 500 is used to cool the coolant in the cooling pipes 201-202;
[0011] The reaction tubes 101-102 pass through the middle holes of the magnetic core 103 and the water-cooling plate 104 and are wound around the magnetic core and the water-cooling plate; the reaction tube inlet end 101 is located at the bottom end of the electrothermal reaction unit and is connected to the pumping device 200; the reaction tube outlet end 102 is located at the top end of the electrothermal reaction unit and is connected to the stirring device 300 through a pipeline;
[0012] The excitation coil 105 is wound around the magnetic core 103 and connected to a power supply device 400; the power supply device 400 is used to provide an excitation voltage, so that the magnetic core 103 generates a time-varying magnetic field as an excitation source, and spontaneously induces an induced voltage and an induced current inside the reaction tubes 101-102;
[0013] The stirring device 300 is connected to the pumping device 200 through a pipeline, and the pipeline of the pumping device contacts the bottom of the container in the stirring device to ensure the pumping of the solution.
[0014] Furthermore, the material of the magnetic core 103 is amorphous nanocrystalline soft magnetic material.
[0015] Furthermore, the length L1 of the magnetic core 103 is 30-100 cm, the width W1 is 15-50 cm, the height H is 3-8 cm, the distance l1 from the middle hole to the width is 5-20 cm, and the distance w1 from the middle hole to the length is 5-20 cm.
[0016] Furthermore, the diameter of the reaction tubes 101-102 ranges from 10 mm to 50 mm.
[0017] Furthermore, the reaction tubes 101-102 are acid- and alkali-resistant glass or silicone tubes.
[0018] The device provided by the present invention is used in the field of wood fiber separation.
[0019] Another aspect of the present invention provides a method for separating all components of wood fiber and improving enzymatic saccharification efficiency, wherein the method is performed using the above-mentioned device for separating all components of wood fiber and improving enzymatic saccharification efficiency;
[0020] The method specifically comprises the following steps:
[0021] (1) washing the wood fiber raw material to remove the ash on the surface, then immersing it in an organic solvent for decolorization, and then drying and crushing it;
[0022] (2) placing the pulverized wood fiber raw material and the dilute acid solution in step (1) into the above-mentioned stirring device, starting stirring to mix, and after the mixture is evenly mixed to obtain a mixed solution, starting a pumping device to send the mixed solution into a reaction tube, and starting a power supply device and a cooling device to react;
[0023] (3) After the reaction of step (2) is completed, the reaction mixture is subjected to solid-liquid separation, the obtained solid is washed to electrical neutrality, and dried to obtain a dry solid residue, and the separated supernatant is hydrolyzed, purified and separated to obtain a crude xylose solid;
[0024] (4) placing the solid residue dried in step (3) and the dilute alkali solution into the above-mentioned stirring device, starting stirring to mix, and after the mixture is evenly mixed to obtain a mixed solution, starting the pumping device to send the mixed solution into the reaction tube, and starting the power supply device and the cooling device to react;
[0025] (5) After the reaction in step (4) is completed, solid-liquid separation is performed, the obtained solid is washed to electrical neutrality, dried to obtain a dry solid residue, the obtained supernatant is separated, the pH is adjusted to 1 to 3 with an acid solution, and the solid component is filtered to obtain lignin;
[0026] (6) The solid residue dried in step (5) is mixed with an acetate buffer solution and cellulase is added to perform enzymolysis to obtain glucose.
[0027] Furthermore, the wood fiber raw material in step (1) includes straw and sawdust.
[0028] Furthermore, the straw includes wheat straw and corn straw.
[0029] Furthermore, the wood chips include poplar wood chips, eucalyptus wood chips, bagasse and bamboo powder.
[0030] Furthermore, the organic solvent in step (1) includes ethanol.
[0031] Furthermore, the mesh size of the pulverization in step (1) is 30 to 80 meshes.
[0032] Furthermore, the dilute acid solution in step (2) includes one or more of dilute sulfuric acid and dilute hydrochloric acid.
[0033] Furthermore, the concentration of the dilute acid solution in step (2) is 0.5%-3%.
[0034] Furthermore, in step (2), the mass volume ratio of the crushed wood fiber raw material to the dilute acid solution is 1 g: 10-50 mL.
[0035] Furthermore, in step (2), the reaction temperature is 90-100° C. and the treatment time is 3-7 h.
[0036] Furthermore, the parameters of the power supply device in step (2) are set to a voltage of 100-800V, a current of 2-10A, and a power of 0.2-8KW.
[0037] Furthermore, in step (2), the ratio of the voltage set by the power supply device to the diameter of the reaction tubes 101-102 is 200-250V:10mm.
[0038] Furthermore, after the power supply device in step (2) is turned on, the magnetic field strength of the magnetic core is 0.5-2T.
[0039] Furthermore, the dilute alkaline solution in step (4) includes one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, sodium bicarbonate, and ammonia water.
[0040] Furthermore, the concentration of the dilute alkaline solution in step (4) is 0.5%-3%.
[0041] Furthermore, the mass volume ratio of the dried solid residue to the dilute alkali solution in step (4) is 1 g:10-50 mL.
[0042] Furthermore, in step (4), the reaction temperature is 50-90° C. and the treatment time is 3-7 h.
[0043] Furthermore, the parameters of the power supply device in step (4) are set to a voltage of 100-800V, a current of 2-10A, and a power of 0.2-8KW.
[0044] Furthermore, in step (4), the ratio of the voltage set by the power supply device to the diameter of the reaction tubes 101-102 is 200-250V:10mm.
[0045] Furthermore, after the power supply device is turned on in step (4), the magnetic field strength of the magnetic core is 0.5-2T.
[0046] Furthermore, the acid solution in step (5) is a sulfuric acid solution with a concentration of 65-80%.
[0047] Furthermore, the acetate in the acetate buffer solution in step (6) includes one or more of sodium acetate, potassium acetate, and ammonium acetate.
[0048] Furthermore, in step (6), the concentration of acetate in the acetate buffer solution is 0.01-0.1 mol / L.
[0049] Furthermore, the mass volume ratio of the dried solid residue to the acetate buffer solution in step (6) is 1 g:30-70 mL.
[0050] Furthermore, in step (6), the amount of cellulase added is 10-30 FPU / g substrate.
[0051] Furthermore, the conditions for enzymatic hydrolysis in step (6) are a temperature of 40-55° C., a rotation speed of 100-150 rpm, and a time of 48-72 h.
[0052] Beneficial Effects
[0053] 1) The present invention provides a new device, in which the electric thermal reaction unit uses induction heat generation, which avoids the energy consumption of medium heat transfer in the traditional hydrothermal treatment process, greatly improves the thermal energy utilization rate, reduces the traditional hydrothermal pretreatment temperature, controls the pretreatment temperature within 100°C, and avoids the requirements for equipment or devices in high temperature and high pressure environments.
[0054] 2) The present invention combines the use of a new device and designs a two-step acid-base coupled electrothermal pretreatment to achieve full component separation of cellulose, hemicellulose and lignin in the wood fiber raw material, and the whole process does not involve the use of organic solvents or catalysts, thereby reducing pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0056] Figure 1 The present invention is a schematic diagram of the overall structure of a device for achieving full component separation of wood fiber and improving enzymatic saccharification efficiency provided in a typical implementation case of the present invention; the diagram includes: an electric heating reaction unit (100), a pumping device (200), a stirring device (300), a power supply device (400), and a cooling device (500).
[0057] Figure 2A typical implementation case of the present invention provides an electrothermal reaction unit in a device for achieving full component separation of wood fiber and improving enzymatic saccharification efficiency, and schematic diagrams of its top view, magnetic core, and water-cooled plate; reaction tubes (101-102), magnetic cores (103), water-cooled plates (104), excitation coils (105), and condensing water pipes (201-202).
[0058] Figure 3 The left side shows the effects of the electrothermal pretreatment and hydrothermal pretreatment on the cellulose retention rate, hemicellulose and lignin removal rate in wood fibers in Example 2 of the present invention and Comparative Example 1. Figure 3 On the right is a comparison chart of enzymatic hydrolysis efficiency.
[0059] Figure 4 The left side shows the effects of the electrothermal pretreatment and hydrothermal pretreatment on the cellulose retention rate, hemicellulose and lignin removal rate in wood fibers in Example 3 of the present invention and Comparative Example 2. Figure 4 On the right is a comparison chart of enzymatic hydrolysis efficiency.
[0060] Figure 5 The left side shows the effects of the electrothermal pretreatment and hydrothermal pretreatment on the cellulose retention rate, hemicellulose and lignin removal rate in wood fibers in Example 4 of the present invention and Comparative Example 3. Figure 5 On the right is a comparison chart of enzymatic hydrolysis efficiency. DETAILED DESCRIPTION
[0061] In view of the deficiencies in the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle will be further explained as follows.
[0062] The technical solution, its implementation process and principles, etc. will be further explained below in conjunction with the accompanying drawings and specific implementation cases. Unless otherwise specified, the power supply device, pumping device, electrothermal reaction unit, stirring device, cooling device, magnetic core, water-cooled plate, etc. used in the present invention are all known to those skilled in the art and can be purchased commercially. The specific product models and structures are not limited here.
[0063] Source of raw materials
[0064] Cellulase (400u / mg) and filter paper enzyme activity (250FPU / g) were purchased from Shanghai Yuanye Biotechnology Co., Ltd.; wheat straw was sourced from Donghai County, Lianyungang City, Jiangsu Province.
[0065] Example 1
[0066] This embodiment provides a device for separating all components of wood fiber and improving the efficiency of enzymatic saccharification, as shown in the attached Figure 1As shown in , its composition includes an electrothermal reaction unit 100, a pumping device 200, a stirring device 300, a power supply device 400, and a cooling device 500.
[0067] In the device, the electrothermal reaction unit 100, as shown in the attached Figure 2 As shown in , its composition includes reaction tubes 101-102, magnetic cores 103, water cooling plates 104 and excitation coils 105. The electrothermal reaction unit 100 is used to generate a time-varying magnetic field as an excitation source, and spontaneously induces an induced voltage and an induced current inside the reaction tubes 101-102. The induced voltage acts on the reaction liquid to produce an electrical effect, and the induced current acts on the reaction liquid to produce a thermal effect, completing the electrothermal coordinated reaction; the pumping device 200 is used to transport the liquid from the stirring device 300 into the reaction tubes 101-102 for electrothermal coordinated reaction; the stirring device 300 is used to stir the liquid to maintain the uniformity of the reaction liquid, and the stirring device 300 is connected to the pumping device 200 through a pipeline, and the pipeline of the pumping device contacts the bottom of the container in the stirring device to ensure the pumping of the solution; the power supply device 400 provides an excitation voltage to the magnetic core 103 through the excitation coil 105; the cooling device 500 is used to cool the cooling water in the cooling tubes 201-202.
[0068] In the electrothermal reaction unit 100, the magnetic core 103 is a rectangular annular plate-shaped magnetic conductive material with a hole in the middle; the water-cooled plate 104 is a rectangular annular plate-shaped metal material with a hole in the middle, which is placed alternately with the magnetic core 103, so as to facilitate the heat energy generated by eddy current loss and hysteresis loss in the magnetic core to be dissipated through the water-cooled plate; cooling pipes 201-202 are embedded in the four sides of the water-cooled plate 104 for cooling water circulation; the water-cooled plate 104 is connected to the cooling device 500 through the cooling pipes 201-202; the reaction tubes 101-102 The middle hole passing through the magnetic core 103 and the water-cooling plate 104 is wrapped around the magnetic core 103 and the water-cooling plate 104; the reaction tube inlet end 101 is located at the bottom end of the electrothermal reaction unit 100, and is connected to the pumping device 200 through a pipeline, so that the pipeline is filled with liquid during transportation; the reaction tube outlet end 102 is located at the top end of the electrothermal reaction unit 100, and is connected to the stirring device 300 through a pipeline, and the liquid is circulated to the stirring device 300; the excitation coil 105 is wrapped around the magnetic core 103 and connected to the power supply device 400.
[0069] The method of using the device is as follows: first, the stirring device 300 is turned on to maintain the uniformity of the reaction liquid, and then the pumping device 200 is started to inject the reaction liquid into the reaction tube 101-102. When the liquid begins to flow out of the reaction tube outlet 102, the reaction tube is filled with liquid. At this time, the power supply device 400 is turned on, and an excitation voltage is provided to the magnetic core 103 through the excitation coil 105. The time-varying magnetic field inside the magnetic core 103 is used as an excitation source to spontaneously induce an induced voltage and an induced current inside the reaction tube 101-102, and an electrothermal coordinated reaction begins. Then, the cooling device 500 is started to circulate cooling water to cool the device. The number of water-cooled plates 104 and magnetic cores 103 can be adjusted according to actual applications.
[0070] Example 2
[0071] This embodiment adopts the Figure 1 and Figure 2 The device shown uses a reaction tube with a diameter of 10 mm, and the material of the reaction tube is silicone; a magnetic core with L1 of 30 cm, l1 of 6 cm, W1 of 18 cm, w1 of 6 cm, and H of 3 cm is used; the size of the water-cooling plate used is equivalent to the size of the magnetic core; the number of magnetic cores in the electrothermal reaction unit used is 3, the number of water-cooling plates is 2, and the water-cooling plate is placed between the two magnetic cores to dissipate heat.
[0072] The method for achieving full component separation of wood fiber and improving enzymatic saccharification efficiency in this embodiment comprises the following steps:
[0073] (1) Dilute acid coupled electrothermal pretreatment: 25 g of crushed wheat straw powder (50 mesh) was mixed with 1 L of dilute sulfuric acid solution (solution concentration was 1%) to obtain a mixed liquid, and then the mixed liquid was placed in a stirring device, and the mixed liquid entered the electrothermal reaction unit through a pumping device for electrothermal cycle treatment (the temperature in the electrothermal cycle treatment was 90° C., and the treatment time was 5 h; the voltage provided by the power supply device was 200 V, the current was 5 A, and the power was 1 KW), and then the treated mixed liquid was subjected to solid-liquid separation, the solid residue (wood fiber) was washed to electrical neutrality, and then air-dried for subsequent dilute alkali pretreatment, and the supernatant was hydrolyzed (121° C., 1 h), rotary evaporated, extracted, and separated to obtain crude xylose solid;
[0074] (2) Dilute alkali coupled electrothermal pretreatment: 25 g of the solid residue after air drying in step (1) was mixed with 1 L of sodium hydroxide solution (solution concentration was 1%) to obtain a mixed liquid, and then the mixed liquid was placed in a stirring device, and the mixed liquid entered the electrothermal reaction unit through a pumping device for electrothermal cycle treatment (the treatment temperature was 70° C., the treatment time was 5 h; the voltage provided by the power supply device was 200 V, the current was 5 A, and the power was 1 KW), and the treated mixed liquid was subjected to solid-liquid separation, the solid residue (wood fiber) was washed to electrical neutrality, and air dried for subsequent enzymatic hydrolysis and saccharification, 72% sulfuric acid solution was added to the supernatant until the pH was 2, and it was left overnight to precipitate lignin, and then vacuum filtered, the retained lignin solid component was washed with acidified warm water, and dried at 50° C. to obtain lignin;
[0075] (3) Enzymatic hydrolysis of wood fiber: The solid residue after air drying in step (2) was mixed with acetate buffer solution (0.05 mol / L) (solid-to-liquid ratio of 1:50) and a certain amount of cellulase (20 FPU / g substrate) was added, and enzymatic hydrolysis was carried out at 50°C and 150 rpm for a period of time (12, 24, 36, 48, 72 h) to obtain glucose and measure the enzymatic hydrolysis rate.
[0076] The cellulose content in untreated wheat straw was 33.3%, the hemicellulose content was 22.7%, and the lignin content was 20.6%; after two-step electrothermal coupled dilute acid-base pretreatment, analysis showed that the cellulose retention rate in the pretreated wheat straw was 76.8%, the hemicellulose removal rate was 89.4%, and the lignin removal rate was 91.7%; the enzymatic hydrolysis rates of the pretreated wheat straw after 12, 24, 36, 48, and 72 hours were 47.5, 67.2, 78.6, 85.9, and 94.1%, respectively.
[0077] Example 3
[0078] The present invention provides Figure 1 and Figure 2 The device shown uses a reaction tube with a diameter of 10 mm, and the material of the reaction tube is silicone; a magnetic core with L1 of 30 cm, l1 of 6 cm, W1 of 18 cm, w1 of 6 cm, and H of 83 cm is used; the size of the water-cooling plate used is equivalent to the size of the magnetic core; the number of magnetic cores in the electrothermal reaction unit used is 3, the number of water-cooling plates is 2, and the water-cooling plate is placed between the two magnetic cores to dissipate heat.
[0079] The method for achieving full component separation of wood fiber and improving enzymatic saccharification efficiency in this embodiment comprises the following steps:
[0080] (1) Dilute acid coupled electrothermal pretreatment: 25 g of crushed wheat straw powder (50 mesh) was mixed with 1 L of dilute sulfuric acid solution (solution concentration was 2%) to obtain a mixed liquid, and then the mixed liquid was placed in a stirring device, and the mixed liquid entered the electrothermal reaction unit through a pumping device for electrothermal cycle treatment (the treatment temperature was 90°C, the treatment time was 3 h; the voltage provided by the power supply device was 200 V, the current was 5 A, and the power was 1 KW), and then the treated mixed liquid was subjected to solid-liquid separation, the solid residue (wood fiber) was washed to electrical neutrality, and air-dried for subsequent dilute alkali pretreatment, and the supernatant was hydrolyzed (121°C, 1 h), rotary evaporated, extracted, and separated to obtain crude xylose solid;
[0081] (2) Dilute alkali coupled electrothermal pretreatment: 25 g of the solid residue after air drying in step (1) was mixed with 1 L of sodium hydroxide solution (solution concentration was 2%) to obtain a mixed liquid, and then the mixed liquid was placed in a stirring device, and the mixed liquid entered the electrothermal reaction unit through a pumping device for electrothermal cycle treatment (the treatment temperature was 70°C, the treatment time was 3 h; the voltage provided by the power supply device was 200 V, the current was 5 A, and the power was 1 KW), and then the treated mixed liquid was separated into solid and liquid, the solid residue (wood fiber) was washed to electrical neutrality, and air dried for subsequent enzymatic hydrolysis and saccharification, 72% sulfuric acid solution was added to the supernatant until the pH was 2, and it was left overnight to precipitate lignin, and then vacuum filtered, the retained lignin solid component was washed with acidified warm water, and dried at 50°C to obtain lignin;
[0082] (3) Enzymatic hydrolysis of wood fiber: The solid residue after air drying in step (2) was mixed with acetate buffer solution (0.05 mol / L) (solid-to-liquid ratio of 1:50) and cellulase (20 FPU / g substrate) was added, and enzymatic hydrolysis was carried out at 50°C and 150 rpm for a period of time (12, 24, 36, 48, 72 h) to obtain glucose and measure the enzymatic hydrolysis rate.
[0083] The cellulose content in untreated wheat straw was 33.3%, the hemicellulose content was 22.7%, and the lignin content was 20.6%; after two-step electrothermal coupled dilute acid-base pretreatment, analysis showed that the cellulose retention rate in the pretreated wheat straw was 74.2%, the hemicellulose removal rate was 90.7%, and the lignin removal rate was 93.5%; the enzymatic hydrolysis rates of the pretreated wheat straw after 12, 24, 36, 48, and 72 hours were 50.2, 69.7, 81.5, 90.6, and 96.9%, respectively.
[0084] Example 4
[0085] The present invention provides Figure 1 and Figure 2The device shown uses a reaction tube with a diameter of 20 mm, and the material of the reaction tube is silicone; a magnetic core with L1 of 60 cm, l1 of 15 cm, W1 of 30 cm, w1 of 10 cm, and H of 5 cm is used; the size of the water-cooling plate used is equivalent to the size of the magnetic core; the number of magnetic cores in the electrothermal reaction unit used is 8, the number of water-cooling plates is 7, and the water-cooling plate is placed between the two magnetic cores to dissipate heat.
[0086] The method for achieving full component separation of wood fiber and improving enzymatic saccharification efficiency in this embodiment comprises the following steps:
[0087] (1) Dilute acid coupled electrothermal pretreatment: 500 g of crushed wheat straw powder (50 mesh) was mixed with 1 L of dilute sulfuric acid solution (solution concentration was 1%) to obtain a mixed liquid, and then the mixed liquid was placed in a stirring device, and the mixed liquid entered the electrothermal reaction unit through a pumping device for electrothermal cycle treatment (the treatment temperature was 90° C., the treatment time was 5 h; the voltage provided by the power supply device was 500 V, the current was 10 A, and the power was 5 kW), and then the treated mixed liquid was subjected to solid-liquid separation, the solid residue (wood fiber) was washed to electrical neutrality, and air-dried for subsequent dilute alkali pretreatment, and the supernatant was hydrolyzed (121° C., 1 h), rotary evaporated, extracted, and separated to obtain crude xylose solid;
[0088] (2) Dilute alkali coupled electrothermal pretreatment: 500 g of the solid residue after air drying in step (1) was mixed evenly with 1 L of sodium hydroxide solution (solution concentration was 1%) to obtain a mixed liquid, and then the mixed liquid was placed in a stirring device, and the mixed liquid entered the electrothermal reaction unit through a pumping device for electrothermal cycle treatment (the treatment temperature was 70° C., the treatment time was 5 h; the voltage provided by the power supply device was 500 V, the current was 10 A, and the power was 5 kW), and then the treated mixed liquid was subjected to solid-liquid separation, the solid residue (wood fiber) was washed to electrical neutrality, and air dried for subsequent enzymatic hydrolysis and saccharification, 72% sulfuric acid solution was added to the supernatant until the pH was 2, and the mixture was left overnight to precipitate lignin, and then vacuum filtered, the retained lignin solid component was washed with acidified warm water, and dried at 50° C. to obtain lignin;
[0089] (3) Enzymatic hydrolysis of wood fiber: The solid residue after air drying in step (2) was mixed with acetate buffer solution (0.05 mol / L) (solid-to-liquid ratio of 1:50) and cellulase (20 FPU / g substrate) was added, and enzymatic hydrolysis was carried out at 50°C and 150 rpm for a period of time (12, 24, 36, 48, 72 h) to obtain glucose and measure the enzymatic hydrolysis rate.
[0090] The cellulose content in untreated wheat straw was 33.3%, the hemicellulose content was 22.7%, and the lignin content was 20.6%; after two-step electrothermal coupled dilute acid-base pretreatment, analysis showed that the cellulose retention rate in the pretreated wheat straw was 78.2%, the hemicellulose removal rate was 88.7%, and the lignin removal rate was 90.3%; the enzymatic hydrolysis rates of the pretreated wheat straw after 12, 24, 36, 48, and 72 hours were 46.5, 64.3, 75.9, 83.1, and 92.7%, respectively.
[0091] Comparative Example 1
[0092] The specific implementation method is the same as Example 2, except that: Comparative Example 1 directly uses a hydrothermal treatment device and a laboratory-level circulating water bath for operation. The specific operation steps are as follows:
[0093] (1) Dilute acid coupled hydrothermal pretreatment: 25 g of crushed wheat straw powder (50 mesh) was mixed with 1 L of dilute sulfuric acid solution (solution concentration was 1%) to obtain a mixed liquid, and then the mixed liquid was placed in a glass bottle and mixed evenly on a magnetic stirring device, and the mixed liquid was pumped into a circulating water bath chamber by a peristaltic pump for hydrothermal circulation treatment (the treatment temperature was 90° C. and the treatment time was 5 h), and the treated mixed liquid was subjected to solid-liquid separation, and the solid residue (wood fiber) was washed to electrical neutrality and dried by forced air for subsequent dilute alkali pretreatment, and the supernatant was hydrolyzed (121° C., 1 h), rotary evaporated, extracted, and separated to obtain crude xylose solid;
[0094] (2) Dilute alkali coupled electrothermal pretreatment: 25 g of the solid residue after air drying in step (1) was mixed with 1 L of sodium hydroxide solution (solution concentration was 1%) to obtain a mixed liquid, and then the mixed liquid was placed in a glass bottle and mixed evenly on a magnetic stirring device, and the mixed liquid was pumped into a circulating water bath chamber by a peristaltic pump for hydrothermal circulation treatment (the treatment temperature adopted was 70° C. and the treatment time was 5 h), and the treated mixed liquid was subjected to solid-liquid separation, the solid residue (wood fiber) was washed to electrical neutrality, and air dried for enzymatic hydrolysis and saccharification, 72% sulfuric acid solution was added to the supernatant until the pH was 2, and the mixture was left overnight to precipitate lignin, and then vacuum filtered, the retained lignin solid component was washed with acidified warm water, and dried at 50° C. to obtain lignin;
[0095] (3) Enzymatic hydrolysis of wood fiber: The solid residue after air drying in step (2) was mixed with acetate buffer solution (0.05 mol / L) (solid-to-liquid ratio of 1:50) and cellulase (20 FPU / g substrate) was added, and enzymatic hydrolysis was carried out at 50°C and 150 rpm for a period of time (12, 24, 36, 48, 72 h) to obtain glucose and measure the enzymatic hydrolysis rate.
[0096] The cellulose content in untreated wheat straw was 33.3%, the hemicellulose content was 22.7%, and the lignin content was 20.6%; after two-step electrothermal coupled dilute acid-base pretreatment, analysis showed that the cellulose retention rate in the pretreated wheat straw was 80.9%, the hemicellulose removal rate was 58.3%, and the lignin removal rate was 64.5%; the enzymatic hydrolysis rates of the pretreated wheat straw after 12, 24, 36, 48, and 72 hours were 22.3, 29.7, 48.1, 62.4, and 69.6%, respectively.
[0097] Comparative Example 2
[0098] The specific implementation method is the same as Example 3, except that: Comparative Example 2 directly uses a hydrothermal treatment device and a laboratory-level circulating water bath for operation. The specific operation steps are as follows:
[0099] (1) Dilute acid coupled hydrothermal pretreatment: 25 g of crushed wheat straw powder (50 mesh) was mixed with 1 L of dilute sulfuric acid solution (solution concentration was 2%) to obtain a mixed liquid, and then the mixed liquid was placed in a glass bottle and mixed evenly on a magnetic stirring device, and the mixed liquid was pumped into a circulating water bath chamber by a peristaltic pump for hydrothermal circulation treatment (the treatment temperature was 90° C. and the treatment time was 3 h), and the treated mixed liquid was subjected to solid-liquid separation, and the solid residue (wood fiber) was washed to electrical neutrality and dried by air for subsequent dilute alkali pretreatment; the supernatant was hydrolyzed (121° C., 1 h), rotary evaporated, extracted, and separated to obtain crude xylose solid;
[0100] (2) Dilute alkali coupled electrothermal pretreatment: 25 g of the solid residue after air drying in step (1) was mixed with 1 L of sodium hydroxide solution (solution concentration was 2%) to obtain a mixed liquid, and then the mixed liquid was placed in a glass bottle and mixed evenly on a magnetic stirring device, and the mixed liquid was pumped into a circulating water bath chamber by a peristaltic pump for hydrothermal circulation treatment (the treatment temperature was 70° C. and the treatment time was 3 h), and the treated mixed liquid was subjected to solid-liquid separation, the solid residue (wood fiber) was washed to electrical neutrality, and air dried for enzymatic hydrolysis and saccharification, 72% sulfuric acid solution was added to the supernatant until the pH was 2, and the mixture was left overnight to precipitate lignin, and then vacuum filtered, the retained lignin solid component was washed with acidified warm water, and dried at 50° C. to obtain lignin;
[0101] (3) Enzymatic hydrolysis of wood fiber: The solid residue after air drying in step (2) was mixed with acetate buffer solution (0.05 mol / L) (solid-to-liquid ratio of 1:50) and cellulase (20 FPU / g substrate) was added, and enzymatic hydrolysis was carried out at 50°C and 150 rpm for a period of time (12, 24, 36, 48, 72 h) to obtain glucose and measure the enzymatic hydrolysis rate.
[0102] The cellulose content in untreated wheat straw was 33.3%, the hemicellulose content was 22.7%, and the lignin content was 20.6%; after two-step electrothermal coupled dilute acid-base pretreatment, analysis showed that the cellulose retention rate in the pretreated wheat straw was 78.5%, the hemicellulose removal rate was 61.4%, and the lignin removal rate was 65.7%; the enzymatic hydrolysis rates of the pretreated wheat straw after 12, 24, 36, 48, and 72 hours were 27.7, 46.8, 61.4, 70.3, and 75.6%, respectively.
[0103] Comparative Example 3
[0104] The specific implementation method is the same as Example 4, except that: Comparative Example 3 directly uses a hydrothermal treatment device, and an industrial-grade reactor is used to replace the hydrothermal treatment device for operation. The specific operation steps are as follows:
[0105] (1) Dilute acid coupled hydrothermal pretreatment: 250 g of crushed wheat straw powder (50 mesh) was mixed with 10 L of dilute sulfuric acid solution (solution concentration was 1%) to obtain a mixed liquid, and then the mixed liquid was placed in a glass bottle and mixed evenly on a magnetic stirring device, and the mixed liquid was pumped into a circulating water bath chamber by a peristaltic pump for hydrothermal circulation treatment (the treatment temperature was 90° C. and the treatment time was 5 h), and the treated mixed liquid was subjected to solid-liquid separation, and the solid residue (wood fiber) was washed to electrical neutrality and dried by air for subsequent dilute alkali pretreatment; the supernatant was hydrolyzed (121° C., 1 h), rotary evaporated, extracted, and separated to obtain crude xylose solid;
[0106] (2) Dilute alkali coupled electrothermal pretreatment: 250 g of the solid residue after air drying in step (1) was mixed with 10 L of sodium hydroxide solution (solution concentration was 1%) to obtain a mixed liquid, and then the mixed liquid was placed in a glass bottle and mixed evenly on a magnetic stirring device, and the mixed liquid was pumped into a circulating water bath cavity by a peristaltic pump for hydrothermal circulation treatment (the treatment temperature adopted was 70° C. and the treatment time was 5 h), and the treated mixed liquid was subjected to solid-liquid separation, the solid residue (wood fiber) was washed to electrical neutrality, and air dried for enzymatic hydrolysis and saccharification, 72% sulfuric acid solution was added to the supernatant until the pH was 2, and the mixture was left overnight to precipitate lignin, and then vacuum filtered, the retained lignin solid component was washed with acidified warm water, and dried at 50° C. to obtain lignin;
[0107] (3) Enzymatic hydrolysis of wood fiber: The solid residue after air drying in step (2) was mixed with acetate buffer solution (0.05 mol / L) (solid-to-liquid ratio of 1:50) and cellulase (20 FPU / g substrate) was added, and enzymatic hydrolysis was carried out at 50°C and 150 rpm for a period of time (12, 24, 36, 48, 72 h) to obtain glucose and measure the enzymatic hydrolysis rate.
[0108] The cellulose content in untreated wheat straw was 33.3%, the hemicellulose content was 22.7%, and the lignin content was 20.6%; after two-step electrothermal coupled dilute acid-base pretreatment, analysis showed that the cellulose retention rate in the pretreated wheat straw was 81.4%, the hemicellulose removal rate was 56.8%, and the lignin removal rate was 63.1%; the enzymatic hydrolysis rates of the pretreated wheat straw after 12, 24, 36, 48, and 72 hours were 18.7, 26.4, 47.2, 60.6, and 67.9%, respectively.
[0109] Table 1 Pretreatment results and enzymolysis rates of Examples 2 to 4 and Comparative Examples 1 to 3
[0110]
[0111] In summary, as shown in Table 1 and Appendix Figures 3 to 5 As shown in, Examples 2, 3, and 4 are compared with Comparative Examples 1, 2, and 3, respectively, and it is found that electrothermal pretreatment is more effective than hydrothermal pretreatment in removing hemicellulose and lignin from wood fibers, and the enzymatic hydrolysis efficiency of wood fibers after electrothermal pretreatment is significantly higher than that of the hydrothermal pretreatment group; the removal rate of hemicellulose and lignin in wood fibers and the enzymatic hydrolysis efficiency of wood fibers are targeted, which proves the advantages of a device and method of the present invention for achieving full component separation of wood fibers and improving enzymatic saccharification efficiency; compared with traditional hydrothermal treatment, the device and method of the present invention also improve energy utilization.
[0112] Comparative Example 4
[0113] This comparative example is a comparison with Example 2. The same device as Example 2 is used, and only the voltage in step (1) is adjusted from 200 V to 400 V. Other operations and parameters remain unchanged.
[0114] Table 2 Pretreatment results of Example 2 and Comparative Example 4
[0115]
[0116] According to Table 2, it can be found that when the voltage is adjusted to 400 V, the response of the thermal effect and the electrical effect is enhanced, and the hemicellulose removal rate in the wheat straw is further improved, indicating that in the device of the present invention, the increase in voltage can more effectively separate hemicellulose.
[0117] Comparative Example 5
[0118] This comparative example is a comparison with Example 2. The same apparatus as Example 2 is used, and only the voltage of step (1) is adjusted from 200 V to 100 V. Other operations and parameters remain unchanged.
[0119] Table 3 Pretreatment results of Example 2 and Comparative Example 5
[0120]
[0121] According to Table 3, it can be found that when the voltage is adjusted to 100V, the pretreatment temperature decreases and the electrical effect weakens, and the hemicellulose removal rate in the wheat straw is greatly reduced, indicating that the voltage selected in the present invention cannot be too small, and the voltage selection range is above 200V.
[0122] Comparative Example 6
[0123] This comparative example is a comparison with Example 2. The same device as Example 2 is used, and only the voltage in step (2) is adjusted from 200V to 500V. Other operations and parameters remain unchanged.
[0124] Table 2 Pretreatment results of Example 2 and Comparative Example 6
[0125]
[0126]
[0127] According to Table 2, it can be found that when the voltage is adjusted to 500 V, although the removal rate of lignin in wheat straw is improved, the content of cellulose and hemicellulose is reduced. This may be because cellulose and hemicellulose are partially degraded under higher thermal and electrical effects. This shows that the voltage selected in the present invention cannot be too high. Therefore, in the device of the present invention, the voltage selection range is between 200 V and 800 V and is adjusted according to the volume of the slurry.
[0128] Comparative Example 7
[0129] This comparative example is a comparison with Example 2. The same device as Example 2 is used, and only the voltage in step (2) is adjusted from 200V to 100V. Other operations and parameters remain unchanged.
[0130] Table 3 Pretreatment results of Example 2 and Comparative Example 7
[0131]
[0132] According to Table 3, it can be found that when the voltage is adjusted to 100 V, the removal rate of lignin in wheat straw decreases, and the cellulose and hemicellulose contents decrease significantly. This is because the lower thermal effect and weaker electrical effect have a poorer effect on the removal of lignin. This shows that the voltage selected in the present invention cannot be too low and needs to be adjusted according to the volume of the slurry.
[0133] It should be understood that the above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for separating all components of wood fiber and improving the efficiency of enzymatic saccharification, characterized in that: The method is carried out using a device for achieving full component separation of wood fiber and improving enzymatic saccharification efficiency, the device comprising an electric heating reaction unit, a pumping device, a stirring device, a power supply device, and a cooling device; The electrothermal reaction unit is composed of a reaction tube, a magnetic core, a water cooling plate and an excitation coil; The magnetic core is a ring-shaped plate-shaped magnetic conductive material with a hole in the middle; the water-cooling plate is a ring-shaped plate-shaped metal material with a hole in the middle, which is placed alternately with the magnetic core; a cooling pipe is embedded in the outer edge of the water-cooling plate for the circulation of cooling liquid; The water-cooled plate is connected to the cooling device through a cooling pipe; the cooling device is used for cooling the coolant in the cooling pipe; The reaction tube passes through the middle hole of the magnetic core and the water-cooling plate and is wound around the magnetic core and the water-cooling plate; the inlet end of the reaction tube is located at the bottom end of the electrothermal reaction unit and is connected to the pumping device; the outlet end of the reaction tube is located at the top end of the electrothermal reaction unit and is connected to the stirring device through a pipeline; The excitation coil is wound around the magnetic core and connected to a power supply device; the power supply device is used to provide an excitation voltage, so that the magnetic core generates a time-varying magnetic field as an excitation source, and spontaneously induces an induced voltage and an induced current inside the reaction tube; The stirring device is connected to the pumping device through a pipeline, and the pipeline of the pumping device contacts the bottom of the container in the stirring device to ensure the pumping of the solution; The method specifically comprises the following steps: (1) washing the wood fiber raw material to remove the ash on the surface, then immersing it in an organic solvent for decolorization, and then drying and crushing it; (2) placing the pulverized wood fiber raw material and the dilute acid solution in step (1) into the stirring device, starting stirring to mix, and after the mixture is evenly mixed to obtain a mixed solution, starting a pumping device to feed the mixed solution into a reaction tube, and starting a power supply device and a cooling device to carry out a reaction; (3) After the reaction of step (2) is completed, the reaction mixture is subjected to solid-liquid separation, the obtained solid is washed to electrical neutrality, and dried to obtain a dry solid residue, and the separated supernatant is hydrolyzed, purified and separated to obtain a crude xylose solid; (4) placing the solid residue dried in step (3) and the dilute alkali solution into the above-mentioned stirring device, starting stirring to mix, and after the mixture is evenly mixed to obtain a mixed solution, starting the pumping device to send the mixed solution into the reaction tube, and starting the power supply device and the cooling device to react; (5) After the reaction in step (4) is completed, solid-liquid separation is performed, the obtained solid is washed to electrical neutrality, dried to obtain a dry solid residue, the obtained supernatant is separated, the pH is adjusted to 1 to 3 with an acid solution, and the solid component is filtered to obtain lignin; (6) The solid residue dried in step (5) is mixed with an acetate buffer solution and cellulase is added to perform enzymolysis to obtain glucose.
2. The method according to claim 1, characterized in that The wood fiber raw materials in step (1) include straw and wood chips; the straw includes wheat straw and corn straw; the wood chips include poplar sawdust, eucalyptus sawdust, bagasse and bamboo powder.
3. The method according to claim 1, characterized in that In step (2), the dilute acid solution includes one or more of dilute sulfuric acid and dilute hydrochloric acid; the concentration of the dilute acid solution is 0.5%-3%; the mass volume ratio of the crushed wood fiber raw material and the dilute acid solution is 1g:10-50mL.
4. The method according to claim 1, characterized in that In step (2), the reaction temperature is 90-100° C. and the treatment time is 3-7 h.
5. The method according to claim 1, characterized in that In step (2), the parameters of the power supply device are set to a voltage of 100-800V, a current of 2-10A, and a power of 0.2-8KW; the ratio of the voltage set by the power supply device to the tube diameter of the reaction tube is 200-250V:10mm; after the power supply device is turned on, the magnetic field strength of the magnetic core is 0.5-2T.
6. The method according to claim 1, characterized in that In step (4), the dilute alkali solution includes one or more of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, sodium bicarbonate, and ammonia water; the concentration of the dilute alkali solution is 0.5%-3%; and the mass volume ratio of the dried solid residue to the dilute alkali solution is 1g:10-50mL.
7. The method according to claim 1, characterized in that In step (4), the reaction temperature is 50-90° C. and the treatment time is 3-7 h.
8. The method according to claim 1, characterized in that In step (4), the parameters of the power supply device are set to a voltage of 100-800V, a current of 2-10A, and a power of 0.2-8KW; the ratio of the voltage set by the power supply device to the tube diameter of the reaction tube is 200-250V:10mm; after the power supply device is turned on, the magnetic field strength of the magnetic core is 0.5-2T.
9. The method according to claim 1, characterized in that In step (6), the acetate in the acetate buffer solution includes one or more of sodium acetate, potassium acetate, and ammonium acetate; the concentration of acetate in the acetate buffer solution is 0.01-0.1 mol / L; and the mass volume ratio of the dried solid residue to the acetate buffer solution is 1 g:30-70 mL.
10. The method according to claim 1, characterized in that In step (6), the amount of cellulase added is 10-30 FPU / g substrate; the conditions for enzymatic hydrolysis are temperature 40-55°C, rotation speed 100-150 rpm, and time 48-72h.
Citation Information
Patent Citations
Method for efficiently separating and enzymolyzing lignocellulose with ionic liquid-high boiling alcohol composite system
CN111154817A
Method for efficiently separating all components of wood fiber
CN111826986A
Method for rapidly separating all components of wood fiber biomass by using alkaline eutectic solvent
CN115142288A
Wood fibrous material coupled enzymatic saccharification method
CN101787384A
Method for promoting degradation of lignocellulose raw material by using MoS2 activated persulfate catalytic system
CN116355977A